Was Weber right? The cultural capital root of socio‐economic growth examined in five European countries. Issue 1 (2014) - ,
Abstract : Purpose – The existing theoretical and empirical research on cultural impact is rather inconsistent. The purpose of this paper is to deal with the reasons for this inconsistency by debating the adequate inclusion of the cultural factor in the growth model and the way to properly measure cultural capital (CC) for this purpose.Design/methodology/approach – The paper starts with analyzing the limitations of growth theory (in particular Paul Romer's endogenous growth model) when CC is not taken into consideration. The amelioration is suggested through involvement of the Weberian mechanism of cultural impact. The difference between Weber's mechanism and using religion as a measurement proxy for cultural attitudes is enlightened. The improvement of Weber's measurement of CC by elevating Pierre Bourdieu's approach to CC from individual to aggregate regional level is suggested. Real data from five EU countries on NUTS II level is addressed for illustrating the above reasoning.Findings – The evidence shows that the suggested by the paper measurement strategy for CC allows for treating culture indeed as a single factor both in theoretical and econometrical sense of the term factor, but without loss of information, which is otherwise inevitable if the author try to approximate culture with a single mono‐dimensional variable such as religion.Originality/value – Through discussion on Rome's endogenous growth model and Weber's cultural mechanisms of impact, the amelioration of growth theory by inclusion of CC is explained, operationalized and applied on a real data example. Acknowledgements : JEL Classifications — Z10, O31, O43, R11